Teaching Ethics in Human Resource Management Education : A Study in Sri Lanka - Opatha, Henarath H. D. N. P. (Prabandhan: Indian Journal of Management, 2021)
The objectives of this paper were to argue richly for the need to learn the topic of ethics in the human resource management (HRM) education, to identify specific topics of ethics to be taught in the HRM education curriculum from the relevant literature, to evaluate and describe the intensity of ethics integration into the HRM curricula of the bachelor’s degrees and full professional qualifications in HRM being offered by universities and professional institutes in Sri Lanka, and to present some suggestions towards improving the effectiveness of teaching ethics in HRM education. This study, being exploratory and descriptive, was carried out by using a desk research based on relevant existent literature, a descriptive analysis of detailed contents of learning materials, an objective evaluation, and a case study analysis. Seven categories of arguments supported to establish the case for learning ethics in HRM education. Five main dimensions of the topic of ethics to be taught were identified. The findings of the evaluation revealed that there is a serious need of ethics integration into the HRM education. The case analysis of the practice of the university which was rated as the highest revealed some useful specific practices for enhancing the effectiveness of teaching ethics in HRM education.